Three telomerases with completely non-telomeric template replacements are catalytically active - Ware, Tracy L. (Oxford University Press, 2000)
Telomerase is a reverse transcriptase minimally composed of a reverse transcriptase protein subunit and an internal RNA component that contains the templating region. Point mutations of template RNA bases can cause loss of enzymatic activity, reduced processivity and misincorporation in vitro. Here we report the first complete replacement of the nine base Tetrahymena thermophila telomerase templating region in vivo with non-telomeric sequences. Rather than ablating telomerase activity, three such replaced telomerases (U9, AUN and AU4) were effective in polymerization in vitro. In vivo, the AU4 and AUN genes caused telomere shortening. We demonstrated the fidelity of the AUN and U9 telomerases in vitro and utilized AUN telomerase to demonstrate that 5′ end primer recognition by telomerase is independent of template base pairing. However, the mutant AUN template telomerase catalyzed an abnormal DNA cleavage reaction. For these U-only and AU- substituted templates, we conclude that base-specific interactions between the telomerase template and protein (or distant parts of the RNA) are not absolutely required for the minimal core telomerase functions of nucleotide addition and base discrimination.